Efficacy and safety of different JAK inhibitors in the treatment of alopecia areata: a network meta-analysis - Wei, Dongfan; Chen, Yi; Shen, Yuqing; Xie, Bo; Song, Xiuzu (Frontiers in Immunology, 2023)
Background: Alopecia areata is an immune system disease characterized by non-scarring hair loss. With the wide application of JAK inhibitors in immune-related diseases, people have begun to pay attention to their role in the treatment of alopecia areata. However, it is not clear which JAK inhibitors are capable of producing a more satisfactory effect on alopecia areata. The aim of this network meta-analysis was to compare the efficacy and safety of different JAK inhibitors in the treatment of alopecia areata. Methods: The network meta-analysis was performed according to the PRISMA guidelines. We included randomized controlled trials in this network meta-analysis, as well as a small number of cohort studies. Differences in efficacy and safety between the treatment and control groups were compared. Results: A total of 5 randomized controlled trials, 2 retrospective experiments and 2 prospective experiments involving 1689 patients were included in this network meta-analysis. In terms of efficacy, oral baricitinib treatment and oral ruxolitinib treatment significantly improved the good response rate of patients compared with placebo，[MD = 8.44, 95% CI (3.63, 19.63)] and [MD = 6.94, 95% CI, (1.72, 28.05)]，respectively. Oral baricitinib treatment significantly improved the good response rate compared with Non-oral JAK inhibitor treatment，[MD=7.56, 95%CI (1.32,43.36)]. Oral baricitinib treatment, oral Tofacitinib treatment and oral ruxolitinib treatment significantly improved the complete response rate compared with placebo, [MD = 12.21, 95% CI (3.41, 43.79)], [MD = 10.16, 95% CI (1.02, 101.54)] and [MD = 9.79, 95% CI, (1.29, 74.27)], respectively. In terms of safety, oral baricitinib treatment, oral tofacitinib treatment and oral ruxolitinib treatment significantly reduced the treatment emergent adverse events rate compared with conventional steroid treatment, [MD = 0.08, 95% CI (0.02, 0.42)], [MD = 0.14, 95% CI (0.04, 0.55)] and [MD = 0.35, 95% CI, (0.14, 0.88)], respectively. Conclusion: Oral baricitinib treatment and oral ruxolitinib treatment seem to be excellent options for the treatment of alopecia areata, due to its good efficacy and reliable safety. Non-oral JAK inhibitors do not appear to produce satisfactory efficacy in the treatment of alopecia areata. However, more experiments are needed to verify the dose selection of JAK inhibitors for treatment.